Women among the Portuguese Immigrants of Lima in the 17th Century - Sullón Barreto, Gleydi (Revista Complutense de Historia de América, 2016)
The passage of women to the Indies was regulated by Law, as applied especially to married men who migrated with their spouses. Documents, nonetheless, reveal the presence of single women and widows who traveled alone or in the company of other relatives. This article focuses on the profile of Portuguese women -or women of Portuguese ancestry- found in Lima in the 17th century. Although they were few with respect to the number of men, as spouses, daughters, nieces or fellow countrywomen they had economic and social impact on the Vice-Royal capital. Some -esepcially those born in Peru- facilitated the processes of integration and insertion of entire families into Lima society. The sources used in this study proceed mainly from the Notarial section of the General Archives of the Nation, in Lima.